AN ANALYASIS OF STUDENTS' SPEAKING ANXIETY IN ELEVENTH GRADE OF MA NURUL ISLAM BELANTARAYA - Hikmatul Maulidia; Syafrizal; Edi Ardian (Program Studi Pendidikan Bahasa Inggris, 2022)
The phenomenon of anxious students often occurs in the process of learning English, especially in class. Where students feel scared and embarrassed when speaking English. The purpose of this study was to determine the extent of students' anxiety level when learning English, in English subjects. At MA Nurul Islam Belantaraya. This research is quantitative descriptive . Instruments This research uses a questionnaire containing 17 statements. And the total population is 36 people, and the sampling technique in this study is the total sampling used in this study is the students / I class XI at MA Nurul Islam Belantaraya kec. Echo. Furthermore, based on the results of calculating student responses to 17 questionnaire statements, students' anxiety levels are in the range of 60% - 79.99% which means High, which means that students' anxiety levels are high in learning English. Based on the results of the study, it can be concluded that the level of student anxiety is caused by a lack of self-confidence, and the high shyness of students in speaking English.